IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTITIES (SAK EMKM) IN PREPARING FINANCIAL REPORTS AT MADINA BAKERY UMKM IN PAYAKUMBUH CITY - Dewi Zahra Puspitasari; Nasfizar Guspendri (Jurnal Akuntansi Syariah (JAkSya), 2026)
The issue in this thesis is that Madina Bakery MSME in Payakumbuh City has not prepared financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The financial records are still maintained in a simple manner, limited to recording cash inflows and cash outflows, and therefore do not yet provide a comprehensive picture of the business’s financial condition. This study aims to examine the implementation of SAK EMKM in the preparation of financial statements at Madina Bakery MSME in Payakumbuh City. The research method employed is field research using a descriptive qualitative approach. The data consist of primary and secondary data obtained through documentation of financial transactions during 2024, as well as interviews with the owner of Madina Bakery MSME in Payakumbuh City. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that Madina Bakery MSME has not optimally implemented SAK EMKM in the preparation of its financial statements. The researcher then prepared a set of financial statements consisting of a statement of financial position, an income statement, and notes to the financial statements in accordance with SAK EMKM. The implementation of SAK EMKM provides a more accurate depiction of the business’s financial condition and can serve as a basis for decision-making and improving the financial performance of MSMEs.